2011
DOI: 10.1007/s10482-011-9636-4
|View full text |Cite
|
Sign up to set email alerts
|

Purification and partial biochemical characterization of a membrane-bound type II-like α-glucosidase from the yeast morphotype of Sporothrix schenckii

Abstract: The early steps of glycoprotein biosynthesis involve processing of the N-glycan core by endoplasmic reticulum α-glucosidases I and II which sequentially trim the outermost α1,2-linked and the two more internal α1,3-linked glucose units, respectively. We have demonstrated the presence of some components of the enzymic machinery required for glycoprotein synthesis in Sporothrix schenckii, the etiological agent of human and animal sporotrichosis. However, information on this process is still very limited. Here, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In addition, NFAg31A was a mesophilic α-glucosidase, being stable up to 41.3 ℃, which is litter higher than 38 ℃ of Lactobacillus johnsonii AG [ 26 ] and 40 ℃ of Schizosaccharomyces pombe AGII [ 34 ], and lower than 55 ℃ of A.cerana AGII [ 32 ]. Whereas, NFAg31A showed an optimal pH at ~ 7.0, which was similar as pH 6.5 to pH 7.5 for most of homologous AGIIs [ 16 , 18 , 29 , 30 , 41 ], AGs [ 13 , 42 ], and human MGAM and SI [ 22 , 43 , 44 ], different with pH 3.5 to 5.5 for A.cerana AGII and archaebacterial AGs. Moreover, NFAg31A was a neutral α-glucosidase, exhibiting well stability over a broad pH range of pH 6.0 to pH 10.0, which was similarly detected as pH 6.2 to pH 9.1 for S.pombe AGII and pH 5.0 to pH 8.0 for L.johnsonii AG.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, NFAg31A was a mesophilic α-glucosidase, being stable up to 41.3 ℃, which is litter higher than 38 ℃ of Lactobacillus johnsonii AG [ 26 ] and 40 ℃ of Schizosaccharomyces pombe AGII [ 34 ], and lower than 55 ℃ of A.cerana AGII [ 32 ]. Whereas, NFAg31A showed an optimal pH at ~ 7.0, which was similar as pH 6.5 to pH 7.5 for most of homologous AGIIs [ 16 , 18 , 29 , 30 , 41 ], AGs [ 13 , 42 ], and human MGAM and SI [ 22 , 43 , 44 ], different with pH 3.5 to 5.5 for A.cerana AGII and archaebacterial AGs. Moreover, NFAg31A was a neutral α-glucosidase, exhibiting well stability over a broad pH range of pH 6.0 to pH 10.0, which was similarly detected as pH 6.2 to pH 9.1 for S.pombe AGII and pH 5.0 to pH 8.0 for L.johnsonii AG.…”
Section: Discussionmentioning
confidence: 86%
“…A distribution analysis of α-glucosidase activity in the yeast morphotype of S. schenckii was carried out by a fluorometric method using 4-methylumbelliferyl-α-D-glucopyranoside (MUαGlc) as a substrate [ 114 ]. The results revealed that 38% and 50% of total enzyme activity were present in a soluble and a mixed membrane fraction (MMF), respectively.…”
Section: Glycosidasesmentioning
confidence: 99%
“…Taken together, these properties are consistent with a type II-like α-glucosidase that was probably involved in N -glycan processing. To our knowledge, this was the first report of this activity in a truly dimorphic fungus [ 114 ].…”
Section: Glycosidasesmentioning
confidence: 99%

Fungal Glycosidases in Sporothrix Species and Candida albicans

Ortiz-Ramírez,
Cuéllar-Cruz,
Villagómez-Castro
et al. 2023
JoF
Self Cite
“…Homologs of these three Am HBGase isoforms (I, II and type II-like HBGases) have also been reported in the yeast Sporothrix schenckii , where they were found to be located in the endoplasmic reticulum and to be involved in processing of the N -glycan core for glycoprotein biosynthesis [12]. However, these three yeast homologs differ in their molecular mass and biochemical characters.…”
Section: Introductionmentioning
confidence: 99%